Towards Digitally Enabled Extension Services: ICT Training Directions in Coastal Odisha (Indian Journal of Extension Education, 2025)
The study was conducted in 2024 to assess the knowledge and accessibility of common ICT tools, training need assessment, and attendance in programs for ICT applications. A total of 248 public extension workers, chosen from four coastal districts, were split into two groups based on their hierarchical responsibilities. While both groups were aware of fundamental ICT tools like PCs and smartphones, there was a notable difference in advanced tools like AI interfaces, drones, and modern digital accessories. While Group 2 (junior officers) demonstrated greater exposure to emerging technology, they were less skilled in basic digital document management, which was prioritized for training. Group-1 members expressed the most prominent training needs in basic troubleshooting and cybersecurity, along with Google tools. There was an overall increasing trend in participation in activities related to ICT applications for years, which showcases a sort of optimism in skills’ upscaling efforts.